Imaging Evaluation of Intrathecal Baclofen Pump-Catheter Systems - Miracle, A.C.; Fox, M.A.; Ayyangar, R.N.; Vyas, A.; Mukherji, S.K.; Quint, D.J. (American Journal of Neuroradiology, 2011)
ITB pumps are widely used in the treatment of intractable spasticity for many clinical indications, including cerebral palsy and spinal cord injury. High-dose intrathecal administration places the patient at significant risk for withdrawal in the event of device malfunction, necessitating rapid and complete evaluation of the pump-catheter system. This article reviews the approach to imaging evaluation of ITB pump-catheter systems, with specific emphasis on radiography, fluoroscopy, CT, and nuclear scintigraphy. APanteroposteriorDTPAdiethylene-triamine pentaacetic acidGABAgamma-aminobutyric acid111InIndium-111ITintrathecalITBintrathecal baclofenTc99mtechnetium-99m